2021
DOI: 10.1111/avj.13058
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens associated with pleuritic pig lungs at an abattoir in Queensland Australia

Abstract: Objective Pleurisy in pigs has economic impacts in the production stage and at slaughter. This study sought to establish if some micro‐organisms can be found in high numbers in lungs with pleurisy by assessing batches of pigs at an abattoir in Queensland Australia. Design Samples of lung (including trachea/bronchus and lymph nodes) from a maximum of 5 pleurisy affected pigs were collected from 46 batches of pigs representing 46 Queensland farms. Procedure Pleurisy‐affected lung areas were cultured by tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Additionally, a large percentage of animals tested positive for M. hyopneumoniae in lung samples across all scores of lesions. In the pleura, an increase in the percentage of positive samples was observed in scores 3 and 4, which is consistent with the findings of Turni, et al [59], who suggested that the prevalence of the pathogen increases with the severity of pleuritis scores. Mycoplasma hyopneumoniae alone causes bronchopneumonia, but when there are coinfections with primary pathogens such as A. pleuropneumoniae or secondary pathogens such as P. multocida, suppurative bronchopneumonia occurs, which is associated with pleurisy [60].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, a large percentage of animals tested positive for M. hyopneumoniae in lung samples across all scores of lesions. In the pleura, an increase in the percentage of positive samples was observed in scores 3 and 4, which is consistent with the findings of Turni, et al [59], who suggested that the prevalence of the pathogen increases with the severity of pleuritis scores. Mycoplasma hyopneumoniae alone causes bronchopneumonia, but when there are coinfections with primary pathogens such as A. pleuropneumoniae or secondary pathogens such as P. multocida, suppurative bronchopneumonia occurs, which is associated with pleurisy [60].…”
Section: Discussionsupporting
confidence: 91%
“…The most common pathogens in lung and pleura samples were G. parasuis and S. suis, and the prevalence of S. suis was also observed in studies conducted in Canada and Australia [59,61]. Ruggeri et al [25] reported that S. suis is associated with pleural and pericardial lesions, mainly in post-weaning pigs.…”
Section: Discussionmentioning
confidence: 86%
“…As with other opportunistic pathogens, P . multocida has the potential to proliferate and infect the lungs when host immunity is compromised due to stress or other pathogens infections [ 6 , 7 ]. Because P .…”
Section: Discussionmentioning
confidence: 99%
“…As an important pathogen of pigs, P . multocida can coinfect with other pathogens including porcine reproductive and respiratory syndrome, porcine circovirus and Mycoplasma hyopneumoniae [ 6 , 7 ]. This coinfection may cause immunosuppression to reduce the host’s immunity and resistance to other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the type of combinations and kind of associated infectious agents vary with local weather conditions, region, and breeding conditions, which generally complicates the severity, prevention, and control of the disease [ 18 ]. P. multocida is one of the most common bacterial agents isolated from respiratory clinical cases worldwide and often is a secondary or opportunistic pathogen of PRDC [ 19 , 20 ]. Five capsular serotypes (A, B, D, E and F) are recognized, with A and D comprising most swine isolates [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%